Effect of Supplementation with Bacillus subtilis in the Diet of Pigs on Protein and Lipid Oxidation of Pork Stored in High-oxygen Modified Atmosphere Packaging - ZHANG Yue, YU Jiang, LIU Fei, ZHANG Yuyu, ZHANG Yimin, MAO Yanwei (Shipin Kexue)
To investigate the effect of dietary addition of Bacillus subtilis on the antioxidant capacity, meat color, protein oxidation, lipid oxidation and sensory quality of pork during storage in high-oxygen modified atmosphere packaging, 12 Duroc × Landrace × Yorkshire pigs were equally allocated into 2 groups that were fed a basal diet alone and in combination with B. subtilis, respectively. Following slaughter, the longissimus dorsi muscle was taken and cut into two parts: one part was used to measure the activity of antioxidant enzymes; the other part was packaged under high oxygen conditions and stored at 4 ℃. The meat color and the contents of malondialdehyde (MDA), carbonyl, and sulfhydryl were measured after 0, 5, 10, 15, and 20 d, and sensory evaluation was performed. The results demonstrated that the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) significantly increased in the B. subtilis supplementation group compared with those in the control group (P < 0.05). Furthermore, dietary supplementation with B. subtilis significantly improved the color of pork stored in high-oxygen modified atmosphere packaging (P < 0.05). During low-temperature storage, dietary supplementation with B. subtilis decreased the MDA content (P < 0.05) and inhibited the lipid oxidation of pork stored in high-oxygen modified packaging. In addition, it significantly inhibited the formation of carbonyl compounds and the loss of sulfhydryl compounds (P < 0.05), and significantly increased the sensory color score of high-oxygen modified atmosphere packaged pork and the overall preference score after opening the package (P < 0.05). In summary, dietary addition of B. subtilis could improve the antioxidant capacity of pork, thereby maintaining the color and inhibiting protein and lipid oxidation in pork stored in high-oxygen modified atmosphere packaging, ultimately enhancing the eating quality of pork.